The Correlation between Duration of Employment, Body Posture and Smoking Habit on Low Back Pain Incidence An Analytic Observational Study Among Taxi Driver in Semarang Municipality - Firmanita, Syifa Dian; Rosdiana, Ika; Indrayani, Ulfah Dian (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2015)
Introduction: Low back pain ((LBP) ranks as number two of neurological disease’s highest prevalence after cephalgia and migraine in Indonesia. Objective: This study aim to determine the relationship between duration of employment, body posture and smoking habit on the incidence of low back pain on taxi driver. Method: This research is an observational analytic cross sectional design. Seventyfour taxi drivers in Semarang municipality was screened with Beck’s Depression Inventory Scale to meet the inclusion and exclusion criteria. Respondents were then given Risk Factor of LBP questionnaire. Data were analyzed with a bivariate correlation test contingency coefficient to see the relationship between duration of employment, body posture, smoking habit and low back pain.Result: the taxi driver with duration of employment >10 years were moderate smokers and having astenis body posture. The analysis of correlation coefficients contingency test showed a significance relationship between duration of employment (p = 0,000), body posture (p = 0,000), and moderate smokers (p=0.010) with the incidence of LBP. Conclusion: the taxi driver with duration of employment >10 years with astenis body posture, and moderate smokers were posstively correlated with LBP.